Requirement for Cell-to-Cell Contact in Epstein-Barr Virus Infection of Nasopharyngeal Carcinoma Cells and Keratinocytes - Chang, Yao (American Society for Microbiology, 1999)
Two nasopharyngeal carcinoma (NPC) cell lines and one keratinocyte cell line could be infected with Epstein-Barr virus (EBV) by cocultivation with virus-producing cells but not by cell-free virus. Using porous culture inserts to manipulate the cell-to-cell contact, we demonstrated that contact between EBV donor B cells and EBV recipient epithelial cells was required for the infection. Cell-to-cell contact not only provided a CR2-independent route of infection but also enhanced CR2-mediated infection in a synergistic manner. Activity of two EBV promoters (Cp and Wp) and expression of EBNA2 were detected in the infected population. A small proportion of the infected cells spontaneously entered an EBV lytic state, which could be induced prominently by chemical treatment. This study provides information on how EBV may infect epithelial cells in vivo, such as at the onset of NPC development.